Association and Expression of CYP2A6 and KIF12 Genes Related to Lamb Flavour and Odour - K. Listyarini; Jakaria Jakaria; M. J. Uddin; C. Sumantri; A. Gunawan (Tropical Animal Science Journal, 2018)
Cytochrome P450, family 2, subfamily A, polypeptide 6 (CYP2A6) and kinesin-like protein KIF12 (KIF12) genes are predicted as candidate genes which play important roles in lamb flavour and odour. The aim of this study was to analyse the genotype polymorphism of CYP2A6 and KIF12 genes, to study association and expression of these genes with lamb flavour and odour. Identification of genes polymorphism and associations of CYP2A6 and KIF12 genes were performed using PCR-RFLP method and GLM analysis. The PCR-RFLP products of CYP2A6 and KIF12 were digested by restriction enzyme BsmAI and BfaI, respectively. The expression of CYP2A6 gene was performed using qRT-PCR. The results showed that the CYP2A6 and KIF12 genes were polymorphics. The CYP2A6 gene found to have two genotypes (TT and GT), whereas the KIF12 gene found to have three genotypes (CC, CT, and TT). The CYP2A6 and KIF12 genes were in Hardy Weinberg Equilibrium (HWE). Association analysis showed that CYP2A6 (g.49170107 G>T) was significantly (P<0.05) associated with 3-methylindole (MI) or skatole, while KIF12 (g.9617965 C>T) was not significantly associated with lamb flavour and odour. The GT genotype exhibited a greater 3-methylindole (MI) or skatole than the TT genotype (P<0.05). The mRNA expression analysis showed that CYP2A6 mRNA expression was higher (P<0.01) in animals with the TT genotype. These results will improve the understanding of the functions of the CYP2A6 in lamb flavour and odour, especially in term of 3-methylindole (MI) or skatole compound within the liver and will shed light on CYP2A6 as a candidate in the selection of sheep with low lamb flavour and odour.